Ketahanan Sosial Masyarakat Banyumas Pada Sektor Pendidikan Dalam Perspektif Reproduksi Sosial - Prastyanti, Shinta - (Jurnal Ketahanan Nasional, 2024)
ABSTRACT The Covid-19 epidemic required strengthening community resilience to adapted to changing social situations. The research aimed to found out the dynamics of social resilience in the Banyumas community through changes in priorities that occured in society, especially those related to education sector, through the perspective of social reproduction.A literature study was employed to answered research questions by analysis of diverse related publications conducted by conceptual approach. The study examined social conditions as the research problem's context, the connectedness across social mobility and schooling, shifts in household educational expenditures, gaps caused by social mobility, and the education system as a whole under the domination of dominant ideas.The study's findings indicated that shifting the focus of household expenditure onto schooling as a social reproduction mechanism failed to always resulted in the predicted vertical social mobility and kept the poorer segments of society in their place, but it was more helpful for the middle class by optimizing resources and access. This condition actually had the potential to worsened the dynamics of social resilience in the Banyumas community in education sector.